Exchange Rate and Trade Balance of East Java Province: J-Curve Evidence and ARDL Approach - Syamad Syamad (East Java Economic Journal, 2025)
The primary objective of this study is to examine the impact of exchange rate fluctuations on the trade balance between East Java Province and its principal trading partners—namely China, Japan, and the United States—while also assessing the presence of the J-Curve phenomenon. The Autoregressive Distributed-Lag model estimation indicates that the exchange rate has an insignificant effect on East Java’s trade balance in the short run, while exerting a statistically significant negative influence in the long run. The empirical findings indicate the absence of a J-Curve phenomenon in East Java’s trade balance with its main trading partners. This outcome implies that the region’s trade flows are predominantly price-inelastic, as exchange rate depreciation fails to generate the expected short-run deterioration followed by long-run improvement. Therefore, currency depreciation is not an effective policy instrument for enhancing export performance, as its benefits are confined to a limited subset of sectors.